Health seeking behavior and reasons for “patient‐related” diagnostic delay among pulmonary tuberculosis suspects attending designated microscopy centre of medical college in rural Puducherry - Subhadra Pranavi, Srikakarlapudi V. V.; Murugan, Venkatesan; Kalaiselvan, Ganapathy (International Journal Of Community Medicine And Public Health, 2017)
Background: The main strategy of modern TB control is early detection and treatment of sources of infection to reduce the duration of infectiousness. Delay in diagnosis has health provider factors and client factors. Health seeking behavior and reasons for TB diagnostic delay is important and which is one of the agenda for operational research under Revised National Tuberculosis Control Program (RNTCP). Methods: The present cross sectional study was conducted among 200 tuberculosis suspects attending the Designated Microscopy centre (DMC) of SMVMCH for a period of 2 months. Data was collected using a pre-designed questionnaire including sociodemographic details, health seeking behaviour, treatment delay and reasons for delay. Collected data was entered and analyzed in EPI_INFO (3.4.3). Descriptive statistics and significant association was established by the use of odd’s ratio with 95% confidence interval. Results: Among the study subjects most of them were between the age group of 15 to 60 years and majority of them were male. Symptoms about tuberculosis was known only to 40(20%) of the suspects and 85(42.5%) accepted that tuberculosis is a curable disease. Among the various factors leading to patient related diagnostic delay age, marital status and multiple symptoms shows significant association. The most common reason for the delay is not aware of the severity of the symptoms 126(63%). Conclusions: There is poor knowledge about tuberculosis, its modes of spread and symptoms among Tb suspects. Patient related delays also common among them which warrant need for public health interventions to improve it.